The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41467-021-22846-1
|View full text |Cite
|
Sign up to set email alerts
|

Structures of flavivirus RNA promoters suggest two binding modes with NS5 polymerase

Abstract: Flaviviruses use a ~70 nucleotide stem-loop structure called stem-loop A (SLA) at the 5′ end of the RNA genome as a promoter for RNA synthesis. Flaviviral polymerase NS5 specifically recognizes SLA to initiate RNA synthesis and methylate the 5′ guanosine cap. We report the crystal structures of dengue (DENV) and Zika virus (ZIKV) SLAs. DENV and ZIKV SLAs differ in the relative orientations of their top stem-loop helices to bottom stems, but both form an intermolecular three-way junction with a neighboring SLA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 56 publications
1
48
0
Order By: Relevance
“…The NS5 RdRp and SLA interaction via the thumb subdomain of RdRp was also suggested by a refined yeast three-hybrid scan [39]. Thus, a model of the NS5 and SLA complex, wherein the 5 terminus of SLA binds the MTase active site and the top stem-loop binds in the thumb subdomain of RdRp was proposed [34]. This model allows the 3 end of viral genome to concomitantly bind to the template-binding channel of NS5 without the need of additional conformational change to accommodate the 3 end of the genome following genome cyclization (Figures 1C and 4B).…”
Section: Sla Promoter-mediated Negative-strand Rna Synthesismentioning
confidence: 95%
See 3 more Smart Citations
“…The NS5 RdRp and SLA interaction via the thumb subdomain of RdRp was also suggested by a refined yeast three-hybrid scan [39]. Thus, a model of the NS5 and SLA complex, wherein the 5 terminus of SLA binds the MTase active site and the top stem-loop binds in the thumb subdomain of RdRp was proposed [34]. This model allows the 3 end of viral genome to concomitantly bind to the template-binding channel of NS5 without the need of additional conformational change to accommodate the 3 end of the genome following genome cyclization (Figures 1C and 4B).…”
Section: Sla Promoter-mediated Negative-strand Rna Synthesismentioning
confidence: 95%
“…The structures show base pairing patterns near the 3-way junction (where the top stem-loop, side loop, and the bottom stem meet) that differ from their predicted secondary structures. In particular, self-complementary side loop sequences are involved in the intermolecular interactions with the side loop of another SLA molecule, rather than participating in the predicted intramolecular base-pair interaction [34]. Further, it was shown that SLA forms a dimer in solution, consistent with the structure, though the function of dimerization is currently unclear [34].…”
Section: Structure Of Viral Rna Promoter Slamentioning
confidence: 99%
See 2 more Smart Citations
“…The vesicle packets contain NS5 (RdRp), NS3 (possessing enzymatic properties: helicase), 5′ RNA-triphosphatase (RTP), a nucleoside triphosphatase (NTPase), and other viral NS proteins in addition to the host factors that catalyze RNA replication, collectively known as the replication complex [ 11 ]. The SLA at 5′UTR acts as a promoter for NS5, the viral RdRp [ 24 ]. The relocation of NS5 to the 3′end is facilitated by cyclization of the genome for the initiation of RNA synthesis.…”
Section: Transmission and Replication Cycle Of Dengue Virus Inside Mammalian Cellmentioning
confidence: 99%